The family Bombyliidae in the Kingdom of Saudi Arabia (Diptera: Brachycera: Asiloidea) - El-Hawagry, Magdi S.; Dhafer, Hathal M. Al (Zootaxa, 2019)
Bombyliidae, also known as "Bee flies", is one of the dipteran families that have species of potential use as biological control agents, as their larvae are predators or parasitoids of eggs, larvae, prepupae or pupae of other insects. The hosts of Bombyliidae are found within six orders of insects: Lepidoptera, Orthoptera, Hymenoptera, Diptera, Coleoptera, and Neuroptera, in addition to the arachnid order Araneae (Spiders). However, almost half of all host records are from bees and wasps (Hymenoptera). The present work provides a catalogue of bee flies (Family Bombyliidae) in the Kingdom of Saudi Arabia. Old World synonymies, type localities, world distributions by biogeographic realm(s) and country, Saudi Arabian localities and dates of collection are provided. A total of 116 species belonging to 40 genera, 12 tribes and 10 subfamilies has been catalogued. Hosts and/or habitat data, where known, are given under the proper genera and/or species. Colored photographs of some species are provided.